The multiplicity of international corporate social responsibility standards: Implications for global value chain governance. Issue 4 (11th October 2019) - Fransen, Luc; Kolk, Ans; Rivera-Santos, Miguel
Abstract : Purpose: This paper aims to examine the multiplicity of corporate social responsibility (CSR) standards, explaining its nature, dynamics and implications for multinational enterprises (MNEs) and international business (IB), especially in the context of CSR and global value chain (GVC) governance. Design/methodology/approach: This paper leverages insights from the literature in political science, policy, regulation, governance and IB; from the own earlier work; and from an inventory of CSR standards across a range of sectors and products. Findings: This analysis' more nuanced approach to CSR standard multiplicity helps distinguish the different categories of standards; uncovers the existence of different types of standard multiplicity; and highlights complex trends in their evolution over time, discussing implications for the various firms targeted by, or involved in, these initiatives, and for CSR and GVC governance research. Research limitations/implications: This paper opens many avenues for future research on CSR multiplicity and its consequences; on lead firms governing GVCs from an IB perspective; and on institutional and market complexity. Practical implications: By providing overviews and classifications, this paper helps clarify CSR standards as "new regulators" and "instruments" for actors in business, society and government. Originality/value: This paper contributes by filling gaps in different existing literatures concerning standard multiplicity. It also specifically adds a new perspective to the IB literature, which thus far has not fully incorporated the complexity and dynamics of CSR standard multiplicity in examining GVCs and MNE strategy and policy.